ANALISIS SWOT PERKEMBANGAN ZAKAT DAN STRATEGI PENGEMBANGAN ZAKAT DI INDONESIA DALAM REVOLUSI ERA SOCIETY 5.0 - Azmi, M.; Susanti, Ratna; Zurkarnaen, Zurkarnaen; Adi Pratama, Mario Rahmad (Journal of Economics and Business, 2023)
Zakat institutions must be managed professionally in accordance with Islamic law, trustworthiness, benefits, fairness, legal certainty, integrated and accountability, so as to increase the effectiveness and efficiency of services in the management of zakat towards good institutional governance (Good Corporate Governacne) with a strategy building a strong foundation in terms of increasing human resources, product development innovation and zakat and waqf programs, harmonization of regulations. In the Era 5.0 revolution, there will be many influences that will occur, that is, with the rapid development of technology, it will facilitate service and management by the amil zakat agency and distribute it to Indonesian people, and the definite target is to improve the quality of human resources with the aim of realizing the ideals of the Indonesian state according to Pancasila important values.